2002
DOI: 10.1073/pnas.102673599
|View full text |Cite
|
Sign up to set email alerts
|

Reversible cardiac fibrosis and heart failure induced by conditional expression of an antisense mRNA of the mineralocorticoid receptor in cardiomyocytes

Abstract: Cardiac failure is a common feature in the evolution of cardiac disease. Among the determinants of cardiac failure, the reninangiotensin-aldosterone system has a central role, and antagonism of the mineralocorticoid receptor (MR) has been proposed as a therapeutic strategy. In this study, we questioned the role of the MR, not of aldosterone, on heart function, using an inducible and cardiac-specific transgenic mouse model. We have generated a conditional knock-down model by expressing solely in the heart an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 30 publications
1
46
1
1
Order By: Relevance
“…84 In contrast, a recent study by Beggah et al 85 reported that expression of MR antisense, and thus knockdown of the MR in cardiac myocytes, produced severe cardiac hypertrophy and fibrosis that was made worse with spironolactone treatment. It has been suggested that this response is not a specific effect of loss of MR signaling but was in large part attributable to the overexpression of a foreign protein in the myocytes, given that very similar heart failure and pathology was seen in cardiac myocyte overexpression of green fluorescent protein 86 or an inflammatory response to the use of antisense.…”
Section: Fuller and Youngmentioning
confidence: 75%
“…84 In contrast, a recent study by Beggah et al 85 reported that expression of MR antisense, and thus knockdown of the MR in cardiac myocytes, produced severe cardiac hypertrophy and fibrosis that was made worse with spironolactone treatment. It has been suggested that this response is not a specific effect of loss of MR signaling but was in large part attributable to the overexpression of a foreign protein in the myocytes, given that very similar heart failure and pathology was seen in cardiac myocyte overexpression of green fluorescent protein 86 or an inflammatory response to the use of antisense.…”
Section: Fuller and Youngmentioning
confidence: 75%
“…Cardiac fibrosis arises after knocking-down the mineralocorticoid receptor (MR) in cardiomyocytes. Surprisingly, restoring the expression of MR protein was sufficient to completely reverse cardiopathy (7). D: brain dysfunction and learning/memory.…”
Section: Invited Reviewmentioning
confidence: 99%
“…Steroid effects will be mediated via the MR also expressed in the tissue. However, this pattern of events has been called into question by Beggah et al 36 They used mice transgenically altered to produce antisense mRNA against the cardiac MR gene in response to a cardiac promoter-specific signal.That is, the animals were subject to a temporally determined, tissue-specific and reversible MR knockout. Paradoxically, this resulted in responses identical to those described above for mineralocorticoid excess.…”
Section: Discussionmentioning
confidence: 99%